The COVID digital home assemblage: Transforming the home into a work space during the crisis. (October 2021) - Watson, Ash; Lupton, Deborah; Michael, Mike
Major changes to home life and work practices globally have been brought about by the COVID-19 crisis. Periods of strict restrictions placed on people's movements outside their homes, aimed at curbing the spread of the novel coronavirus, have meant that the home was requisitioned as a primary site for work for many people. In this article, we draw on case studies from an ethnographic project that explored how people living in Sydney use digital technologies in the home setting. Our fieldwork commenced in early 2020, just prior to the national COVID lockdown period in Australia, and continued throughout the lockdown and the months following. As a result, we were able to document people's experiences of transitioning to working from home during the first year of the pandemic. In this article, we adopt a sociomaterial approach together with domestication theory to analyse the complexities of the changed COVID home in the context of digitised working arrangements. We surface and theorise the tensions and leaky boundaries between workplaces and family/domestic life that are brought about by, through and beyond the digital. By addressing the sociomaterial choreographies and modalities of presence involved, we attempt to capture the processes through which the COVID digital home assemblage is continuously configured and the more or less simultaneous presence and absence of people in both domestic and work domains.